“ISLAMIC GUIDING BOOK” Mata Kuliah Agama sebagai Upaya Penanaman Nilai Karakter Jujur dan Disiplin Beribadah Mahasiswa Universitas Wiraraja - Imam Hanafi; Eko Adi Sumitro (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2020)
This study aims to look at several things related to student religious activities as outlined in the book "Islamic Guiding Book". In addition to filling out their daily worship activities, students are also asked to conduct their own evaluation of the notes contained in the book to continue to be better. To find out how far the students' honesty level is, the researcher uses case study research. The data collection technique used by the researcher is through observation and assessment of students' personal records and making observations both directly and indirectly.